(untitled) (Fiep Bulletin - online, 2011)
The different courses of Orientation in official measures vary between 12 min and 80 min of independent duration of the distance, in other words, the official rules extol the time of duration of the proofs and not the distance. An elite athlete, masculine, was monitored during a Orienteering sprint race. The data were analyzed through the software Quick Route. The results showed that the need of a good anaerobic shape of the athlete of high revenue exists and that the interaction of the anaerobic capacity and the different possibilities of muscular recruitment are factors that have influency in the athlete’s performance.